Rationale for selecting organizational and technological solutions - Oleynik, Pavel; Doroshin, Ivan; Kazaryan, Ruben; Avetisyan, Robert (Edelweiss Applied Science and Technology, 2024)
Two approaches to choosing the optimal solutions are considered – the mathematical approach and the applied approach. The mathematical approach is presented as determining the extremum of a function on the considered segment. The applied approach is presented in the form of existing various assessments of organizational and technological solutions. A list of the main, local and individual indicators used for this, along with their combinations, is given. The paper substantiates the fundamental differences in the processes of optimization of organizational and technological solutions in the mathematical and applied approaches with the conclusion that it is inappropriate to use the term “optimization of organizational and technological solutions” in applied research. Synonyms for this term are proposed and the concept of “optimization of organizational and technological solutions” is adjusted. The paper highlights the current practice of conducting a thorough evaluation of organizational and technological solutions, which has proven to be effective in coordinating the construction of specific entities and their interconnected systems. This approach aids in creating a unified project for managing tasks within a construction company’s production program, as well as in crafting documentation for operational and production planning purposes.